Proceedings of the 50th ACM Technical Symposium on Computer Science Education 2019
DOI: 10.1145/3287324.3287346
|View full text |Cite
|
Sign up to set email alerts
|

Building Computational Creativity in an Online Course for Non-Majors

Abstract: In recent years, a growing number of universities have begun to offer specialized courses as a way to make computer science (CS) more accessible to students with little or no prior CS or programming experience, especially non-CS majors. One of the ways courses have been modified for these students is by supplementing the core problem solving and coding aspects of the curriculum with explicit instruction on computational thinking principles. These "computational thinking" courses are promising in that they grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Most studies describe positive effects of their interventions. A number of studies evaluated the CT skills and found improvement on post-tests (both self-assessment and actual skill tests) [2,15,17,32,45,47,49,51,63,67,69], a relation between the number of assignments completed and an increase in CT skills [44,60], increased awareness of using CT skills [37,41], and evidence of CT skills through an investigation of programming concepts used in Scratch [23]. Studies also describe improved understanding of CT [13,17,20,31,47,50,73,74], and conclude that the attitude towards CT was improved by the intervention [47,57,59,64,73,74].…”
Section: Results On Effectiveness Of Ct Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies describe positive effects of their interventions. A number of studies evaluated the CT skills and found improvement on post-tests (both self-assessment and actual skill tests) [2,15,17,32,45,47,49,51,63,67,69], a relation between the number of assignments completed and an increase in CT skills [44,60], increased awareness of using CT skills [37,41], and evidence of CT skills through an investigation of programming concepts used in Scratch [23]. Studies also describe improved understanding of CT [13,17,20,31,47,50,73,74], and conclude that the attitude towards CT was improved by the intervention [47,57,59,64,73,74].…”
Section: Results On Effectiveness Of Ct Interventionsmentioning
confidence: 99%
“…Different options to teach CT without programming have been used in the studies. Examples of these are using computational creativity exercises [47,60], paper-and-pencil or unplugged activities [15,31,40,59], and simulation environments [28]. Content-wise the assignments are again very different.…”
Section: Ct Interventions In Higher Educationmentioning
confidence: 99%
“…Além dos métodos tradicionais de coleta de dados, existem métodos que foram desenvolvidos para avaliar e mensurar o desenvolvimento do Pensamento Computacional. Román-González et al [16] desenvolveu o Computational Thinking Test (CTt), que avalia os laços, direções, funções condicionais e simples, enquanto Peteranetz et al [14] desenvolveram um teste com 18 itens para medir as habilidades de Pensamento Computacional, os itens mediram abstração, generalização, decomposição, reconhecimento de padrões e algoritmos. Para mensurar o desenvolvimento do Pensamento Computacional, esse teste deve ser aplicado duas vezes, a primeira no início do semestre e a segunda no fim, de modo a verificar o progresso dos estudantes durante o semestre.…”
Section: Generalizaçãounclassified
“…For example, Miller (2013) determined that creative thinking training improves computational thinking skills. Similarly, Peteranetz, Soh, and Ingraham (2019) determined that students who received computational creativity training improved their computational thinking knowledge level and computational thinking practices. In future studies, computational thinking skills and creativity of gifted students can be examined in detail with experimental research models.…”
Section: Extended Abstractmentioning
confidence: 99%